STRATEGI MENINGKATKAN HASIL BELAJAR GEOGRAFI MELALUI PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS XII IPS-3 SMAN 2 MAJENE SULAWESI BARAT) - Zhiddiq, Sulaiman; Syamsul, Putri A; Syarif, Erman; Yusuf, Muhammad; Mannan, Abdul (Social Landscape Journal, 2024)
This Classroom Action Research aims to determine whether the application of the discovery learning model can improve the geography learning outcomes of students of class XII-IPS3 SMAN 2 Majene. Initial observations showed that the learning process was less dynamic, the students' learning outcomes had not met the KKM, besides that because they had not or did not use a learning model. Therefore, this research took the topic of applying the discovery learning model in the hope of improving learning outcomes. The results of this study showed an increase in learning outcomes by using the discovery learning model seen from the average value of learning outcomes in cycle I which was 75.86 with a percentage of classical learning completeness of 31.03% then increased in cycle II with an average value of 88.62 with a percentage of classical learning completeness of 86.20%.